2023
DOI: 10.1084/jem.20221111
|View full text |Cite|
|
Sign up to set email alerts
|

Inflammatory and tolerogenic myeloid cells determine outcome following human allergen challenge

Abstract: Innate mononuclear phagocytic system (MPS) cells preserve mucosal immune homeostasis. We investigated their role at nasal mucosa following allergen challenge with house dust mite. We combined single-cell proteome and transcriptome profiling on nasal immune cells from nasal biopsies cells from 30 allergic rhinitis and 27 non-allergic subjects before and after repeated nasal allergen challenge. Biopsies of patients showed infiltrating inflammatory HLA-DRhi/CD14+ and CD16+ monocytes and proallergic transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Macrophages were identified for three phenotypes, M1, M2, and MDSC, in healthy people and periodontitis patients ( Figures 6A, B ). MDSCs were characterized by the lowest levels of HLA-DRA along with the highest levels of S100A8 , S100A9 , S100A12 and CXCL8 ( Umansky et al, 2016 ; Voskamp et al, 2023 ) ( Supplementary Figure S4 ). Our study found that the periodontitis group had three trajectories, M1, M2, and MDSC, while the healthy group only had two trajectories ( Figures 6C, D ).…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages were identified for three phenotypes, M1, M2, and MDSC, in healthy people and periodontitis patients ( Figures 6A, B ). MDSCs were characterized by the lowest levels of HLA-DRA along with the highest levels of S100A8 , S100A9 , S100A12 and CXCL8 ( Umansky et al, 2016 ; Voskamp et al, 2023 ) ( Supplementary Figure S4 ). Our study found that the periodontitis group had three trajectories, M1, M2, and MDSC, while the healthy group only had two trajectories ( Figures 6C, D ).…”
Section: Resultsmentioning
confidence: 99%
“…Myeloid-derived suppressor cells (MDSCs) consist of myeloid-derived myeloid progenitor cells and immature cells; MDSC expression was markedly increased in acute inflammation, severe infections and tumors, and negatively regulates immune function, a recent study showed that MDSCs are engaged in the invigoration of Th2 cells, which induces airway hyperresponsiveness and asthma, and MDSC levels have been reported in AR, AS, and other allergic diseases. Elevated MDSC is reported in AR, AS, and other allergic diseases, but MDSC expression is also elevated in healthy individuals after exposure to allergens, suggesting the possibility that MDSCs may have both inhibitory and pro-validating roles, and that the roles of different phenotypes of MDSCs and chemokines may be the key factors influencing the function of MDSCs ( 54 ).Our research only found that one MDSC phenotype has a protective effect against AAD (CD14 on Mo MDSC, p IVW-AR = 0.025, beta AR = -0.032, OR AR = 0.968). No other causal relationship between MDSCs and AAD was identified.…”
Section: Discussionmentioning
confidence: 99%
“…In allergic asthma, both cDC1s and cDC2s were found to be increased in induced sputum after allergen inhalation [ 113 , 114 ]. A single-cell proteomic and transcriptomic profiling of nasal biopsies demonstrated a different behavior of cDC2 from allergic vs. non-allergic patients, characterized, respectively, by inflammatory vs. inhibitory/tolerogenic transcriptional changes upon allergen challenge [ 115 ]. Mice lacking lung DCs failed to initiate and to perpetuate allergen-driven airway inflammation [ 116 , 117 , 118 ].…”
Section: Pathological Role Of Dcs In Respiratory Diseases and Implica...mentioning
confidence: 99%